2012
DOI: 10.2527/jas.2011-4375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zilpaterol hydrochloride and days on the finishing diet on feedlot performance, carcass characteristics, and tenderness in beef heifers1

Abstract: British × Continental heifers (n = 3,382; initial BW = 307 kg) were serially slaughtered to determine if increasing days on the finishing diet (DOF) mitigates negative consequences of zilpaterol HCl (ZH) on quality grade and tenderness of beef. A 2 × 3 factorial arrangement of treatments in a completely randomized block design (36 pens; 6 pens/treatment) was used. Zilpaterol HCl (8.33 mg/kg DM) was fed 0 and 20 to 22 d before slaughter plus a 3 to 5 d withdrawal to heifers spending 127, 148, and 167 DOF. Feedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
39
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 16 publications
19
39
1
1
Order By: Relevance
“…The magnitude of improvement in final body weight (22 %), lies near the maximum value reported in the literature (25 %), using the reference brand ZH. 4,[31][32][33][34][35][36][37][38][39] For example, weight gain coincides greatly with other studies conducted on Bos taurus bulls. 34,40 Elam et al treated Bos taurus bulls with 8.33 mg ZH/kg feed as dry matter for 30 days and obtained final weight increments of 9.3 kg compared with untreated bulls.…”
Section: Generic Zilpaterol Hcl In Bos Indicussupporting
confidence: 85%
“…The magnitude of improvement in final body weight (22 %), lies near the maximum value reported in the literature (25 %), using the reference brand ZH. 4,[31][32][33][34][35][36][37][38][39] For example, weight gain coincides greatly with other studies conducted on Bos taurus bulls. 34,40 Elam et al treated Bos taurus bulls with 8.33 mg ZH/kg feed as dry matter for 30 days and obtained final weight increments of 9.3 kg compared with untreated bulls.…”
Section: Generic Zilpaterol Hcl In Bos Indicussupporting
confidence: 85%
“…When ZH was added to the GP program and compared to the CON carcasses, HCW, yield grade, and LM area were increased by 5%, 33%, and 18%, respectively. The increase in HCW is comparable to other studies Robles-Estrada et al, 2009;Rathmann et al, 2012); however, the increase in LM area and yield grade are much greater than these studies, which may be due to the combination of GP utilized in the COMBO treatment. Montgomery et al (2009) found that heifers supplemented ZH without being administered anabolic implants had only a 9% increase in LM area and yield grade when compared to heifers not subjected to GP technologies.…”
Section: Growth-promoting Technologies Effectssupporting
confidence: 79%
“…In agreement with the current study, Garber et al (1990) found that implanting heifers with Synovex-H did not affect G:F; however, ADG was improved by the implant. The addition of ZH to feedlot diets provides equally impressive results by increasing ADG and G:F by up to 18% and 25% , respectively Rathmann et al, 2012). In the current study, combining the implant regimen with ZH did not improve feedlot performance of the heifers when compared to controls; however, the magnitude of increase in ADG and G:F were similar to improvements reported in literature (22% and 18%, respectively).…”
Section: Growth-promoting Technologies Effectsmentioning
confidence: 99%
See 2 more Smart Citations